Assessing farmers’ knowledge and socioeconomic impacts of the cocoa hand pollination programme: The case of the Atwima Nwabiagya District, Ghana - Ameyaw, Kenneth (University of Cape Coast, 2023)
Cocoa is one of Ghana's leading products, contributing significantly to the world market. In the past, Ghana held the top position as the leading cocoa producer, supporting millions of jobs in the cocoa sector. However, the current cocoa production has seen a decline attributed to various factors, including pest and disease infestations, poor maintenance, an ineffective extension system, and inadequate cocoa production practices. This study focuses on understanding farmers' knowledge and perceptions of hand pollination and its impact on cocoa yield and farm practices in the Atwima Nwabiagya district. Using structured questionnaire, 388 cocoa farmers were selected using the simple random sampling procedure. The descriptive cross-sectional design was employed. The data was analysed using both descriptive and inferential statistical approach. The findings revealed that Cocoa farmers in the Atwima Nwabiagya district had high knowledge level on hand pollination of cocoa. The finding showed that the adoption of hand pollination of cocoa leads to an increase in farmers’ productivity/yield and increased annual earnings. Also, the results showed that the adoption of hand pollination had significant impact on their livelihoods. Farmers reported to possess high human, social, physical, natural, and financial capital after adopting hand pollination method. Finding from the study have implications for policy and practices cocoa pollination and production in Ghana. For instance, Government through COCOBOD must establish tailored credit and savings schemes, facilitate access to financial services such as micro-credit and agricultural loans to farmers who adopt hand pollination in order to enable them make necessary investments in their farms
x,82p:,ill.